More Missiles Than Megawatts. - Ramana, M.V.
For a developing country, India has pursued a uniquely ambitious and far-reaching nuclear technology program. During the last six decades, it has developed expertise and facilities covering the entire nuclear fuel cycle, from uranium mining and milling to reprocessing spent nuclear fuel. India also operates a pilot fast breeder reactor, one of seven countries to have built one, and it has started constructing an industrial-scale breeder.
Keywords: India; U - Element; Industrial scale breeder; Megawatts; Missiles; Nuclear fuel cycle; Nuclear technology program; Pilot fast breeder reactor; Uranium milling; Uranium mining